Entering into sponsorship agreements. Perspectives for charitable works of the Church in Poland - KALETA, PAWEŁ (Prawo Kanoniczne, 2019)
This study explores the usage of sponsorship agreements as new forms of governance and funding in the delivery of educational and social welfare services which are struggling to support themselves. Sponsorship agreements were developed by religious institutes in the North America which founded charity entities. Significant changes affecting healthcare delivery, led leaders and managers of Catholic healthcare institutions to draw up appropriate sponsorship agreements so as to assure their Catholic identity and the charism of their works. This article aims to show the ways in which a sponsorship agreement may be drawn up in order to enable a church entity to carry out its charitable works effectively. The author commences with great focus on canon law and the legal definition of “sponsorship” in order to further determine the necessary requirements to establish public juridic persons for healthcare ministry. The requirements of Catholic healthcare agreements provide the crucial part of the text. This includes the following elements: 1) Catholic mission; 2) Catholic identity; 3) compliance with canon law; 4) ownership; and 5) reserved powers. These elements should be taken into account especially when sponsorship agreements involve non Catholic parties. The analysis of sponsorship agreements is based on the new legal arrangements developed in the U.S.A. and in Canada. Its purpose is to provide practical guidance for sponsorship agreements in Poland, which is yet unknown both in civil and canon law. This article provides practical guidance for sponsorship agreements that are constantly affected by numerous social and economic changes.